2014
DOI: 10.1118/1.4873333
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and patient exposure as well as image quality for full spine examinations with the EOS imaging system

Abstract: As a summary, the estimated effective dose was 290 μSv for an adult; the image quality remains comparable to conventional systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 15 publications
3
40
0
Order By: Relevance
“…We did not perform such simulation in our study. Other studies have shown that with a mean entrance dose of 181 and 316 Gy with SSS and DFD respectively, effective doses range from 0.08 to 0.20 mSv [5,[19][20][21][22][23]. Given the skin entrance dose observed in our study, the dose ratio is better for the SSS.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We did not perform such simulation in our study. Other studies have shown that with a mean entrance dose of 181 and 316 Gy with SSS and DFD respectively, effective doses range from 0.08 to 0.20 mSv [5,[19][20][21][22][23]. Given the skin entrance dose observed in our study, the dose ratio is better for the SSS.…”
Section: Discussionmentioning
confidence: 53%
“…The DQE standard from IEC mentions specifically that DQE is not suited and should not be evaluated for systems in which the X-ray field is scanned across the patient [25]. Evaluating SSS, Damet et al found a DQE peak around 13% (RQA5 and RQA7), but confirmed that DQE for SSS must not be directly compared to DQE values for 2D radiography systems [23]. Therefore, in our study we evaluated the quality of the two systems with another parameter, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…We have been using the EOS scanner for full-spine examinations at our institution, since the fall of 2014. The EOS scanner uses a biplanar slot-scanning technology, which has been described in detail elsewhere [7][8][9][10] . The original version of the system had a standard low-dose protocol.…”
Section: Introductionmentioning
confidence: 99%
“…with regards to skin entrance dose 7,9,11 ; however, only a few studies have evaluated organ dose and full-body absorbed dose (effective dose) [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the noise at the detector is a combination of quantum and electronic noise that can be described, respectively, by Poisson and Gaussian distributions. However, as shown by Damet et al (2014), in EOS images the quantum noise contribution is predominant and, even at very low doses, the electronic noise is negligible. Therefore, the noise model can be approximated by a Poisson distribution.…”
Section: Noise Model Estimationmentioning
confidence: 94%